Incorporating the Wasatiyyah concept to improve financial decision of Muslim consumers - Ramlee, Roslily; Syed Mohd. Zain, Sharifah Raihan; Wan Hussain, Wan Rohaida (2019)
The statistics and survey of literature outline existence of a massive problem in financial prudence of Malaysians, and in some cases Muslims. One aspect is glaringly imminent that a lack of spiritual/religious interventionist approach exists in exploring the lack of awareness among consumers that led to the present situation. Instead of attempting to solve the ordeal described above through brute economic policies, a wasatiyyah oriented approach is warranted in informing the consumers of their religious obligation to avoid profligate spending and adopting moderation in financial matters. Besides wasatiyyah is a present national agenda of the Malaysian government. Hence, the objective of this study is to examine the adoption of wasatiyyah concept among Muslims consumers with different level of financial literacy and personal characteristics. Primary data was collected through a self-administrated survey on selected group of Muslim consumers. Relevant statistical software was employed to perform exploratory factor analysis through Principal Component Analysis (PCA), Confirmatory Factor Analysis (CFA), and second-order invariance analysis on the data collected. From 299 respondents, generally the finding shows that consumers who adopted wasatiyyah concept will be more conscious in their financial decision and more caution in their credit management and consequently spend according to their means. Implicitly, by adopting the wasatiyah concept it will alleviate the excessive exposure to debt which may lead to bankruptcy and causing problem to the financial system and the Malaysian economy in general.